Penerapan Manipulasi Kain Teknik Burnt Fabric pada Jaket Look Streetwear - Nina Silfiyani; Romadhona Chusna Tsani (Garina, 2025)
The innovations in the fashion world appears according to technological advances that always bring up new ideas. For example, ready-to-wear clothing that has several looks, one of which is streetwear. The application of burnt fabric is to combine elements of the burnt fabric technique (pembakaran kain) in ready-to-wear look streetwear, the application of the burnt fabric technique aims to create new creations and new patterns on streetwear clothing. The method used in this study is a qualitative method, observation, documentation, literature, and analysis. The results of this final project are ready-to-wear clothing with a streetwear look given variations of burnt fabric on the jacket. The making of this burnt fabric requires high concentration and accuracy. The conclusion from the application of burnt fabric is that the fabric used in the making of burnt fabric takes a big effect on the final result of the burnt fabric. If using a plastic textured cloth, it cannot be burned and produces lumps or will melt. From taking this title, the writer hopes that it can be useful for the fashion world, inspire fashion creation, and create new opportunities in the fashion world. Suggestions for making burnt fabric on jackets, it would be better to use a pattern first so that the burnt fabric motif is organized and according to the design.